2009
DOI: 10.1063/1.3147198
|View full text |Cite
|
Sign up to set email alerts
|

Improving lateral resolution of electrostatic force microscopy by multifrequency method under ambient conditions

Abstract: Articles you may be interested in I-V characteristics of single and clustered ligand stabilized cobalt nanoparticles on highly oriented pyrolytic graphite obtained with conducting atomic force microscopy under ambient conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…Second, ω 2 is more sensitive to changes in force gradient than ω 1 because the minimal detectable force gradient is inversely proportional to the frequency and the Q-factor of the resonance peak, which is higher at ω 2 (Q(ω 2 ) ~500) than at ω 1 (Q(ω 1 ) ~170) (Hoummady and Farnault, 1998). Third, the contribution of the electrostatic interaction between the cantilever and the sample to the electrostatic force is minimized at ω 2 , thereby enhancing spatial resolution in the DREEM image (Ding et al, 2009). Fourth, higher eigenmodes provide enhanced phase contrast compared to the fundamental mode of tip oscillation for both AFM and EFM imaging (Martínez et al, 2008; Stark et al, 1999; Thompson et al, 2013).…”
Section: Designmentioning
confidence: 99%
“…Second, ω 2 is more sensitive to changes in force gradient than ω 1 because the minimal detectable force gradient is inversely proportional to the frequency and the Q-factor of the resonance peak, which is higher at ω 2 (Q(ω 2 ) ~500) than at ω 1 (Q(ω 1 ) ~170) (Hoummady and Farnault, 1998). Third, the contribution of the electrostatic interaction between the cantilever and the sample to the electrostatic force is minimized at ω 2 , thereby enhancing spatial resolution in the DREEM image (Ding et al, 2009). Fourth, higher eigenmodes provide enhanced phase contrast compared to the fundamental mode of tip oscillation for both AFM and EFM imaging (Martínez et al, 2008; Stark et al, 1999; Thompson et al, 2013).…”
Section: Designmentioning
confidence: 99%
“…The above results suggest that a higher measurement frequency leads to a decreased cantilever-sample effect, resulting in better lateral resolution for potential measurements in KPFM. In previous studies, cantileversample interactions in lift-mode AM-KPFM were decreased by using the second resonance frequency in the potential measurements, leading to better lateral resolution [15,16]. The probe-sample interactions were estimated from a simple cantilever-sample and tip-sample capacitance model.…”
Section: Resultsmentioning
confidence: 99%
“…The signs of the capacitance gradients C ′ 2−1 and C ′ 2−2 are opposite, therefore, C ′ cantilever (ω 2 ) is smaller than C ′ cantilever (ω 1 ). Ding et al reported the ca- pacitance models for the first and second eigenmodes, and described that the second eigenmode led to a decreased cantilever-sample capacitive effect and an increased tipsample effect [16]. Similarly, opposition between C ′…”
Section: Resultsmentioning
confidence: 99%
“…More recently, another AFM-based potential detection technique was developed for electrostatic force imaging by analyzing the resonant frequencies. Specifically, electrostatic force microscopy operated in multifrequency mode, provides a promising technique for improving the spatial resolution and time resolution [43], and can be applied to obtain electrostatic and topographic images simultaneously [44,45].…”
Section: Kelvin Probe Force Microscopy (Kfm)mentioning
confidence: 99%